Improving Social Relations Between Students Through Learning Dayak Music Ensembles Using the Peer Tutor Method - Sagala, Mastri Dihita (Universitas Tanjungpura, 2024)
Preserving Dayak culture and developing musical abilities among the younger generation are important aspects in the revitalization of society. Learning Dayak music ensembles can help students to improve their social skills more effectively, so that they can be more calm, focused and productive in making music. This research used a qualitative descriptive method involving first semester students of the Performing Arts Education Study Program. Dayak music ensemble learning is carried out once a week. This learning includes theoretical and practical material for playing Dayak musical instruments, such as dau, gedobokng and agukng. These three instruments are often found in accompanying music for Dayak traditional ritual ceremonies. Learning activities take the form of exercises in ensemble format so that in the process students need to interact and socialize in order to be able to play music correctly. The development of students' social skills is obtained through observation, interviews and documents. Data analysis shows that the peer tutoring method makes a significant contribution to the development of social skills among students. This technique is used to determine aspects of social abilities, such as the ability to communicate, collaborate, leadership and responsibility effectively. The findings of this research contribute to the development of structured Dayak music ensemble learning strategies to improve students' social abilities which are reflected in aspects of social sensitivity, the emergence of a sense of empathy and self-confidence. Additionally, these findings highlight the transformative power of peer mentoring in fostering social-emotional development and musical skills.